ANALISIS YURIDIS ATAS PERTANGGUNG JAWABAN NOTARIS TERHADAP AKTA FIDUSIA YANG DIBUAT SETELAH TERBIT PERMENKUMHAM NOMOR 9 TAHUN 2013 TENTANG PENDAFTARAN FIDUSIA ELEKTRONIK - CIPTO SOENARYO (PREMISE LAW JURNAL, 2015)
A Notary is a public official who has the authority to draw up authentic deeds and other authorities under this law. He also has the authority under Law No. 30/2004 in conjunction with Notarial Act No. 2/2014 and Law No. 42/1999 on Fiduciary about drawing up fiduciary collateral deed, and based on the Decree of the Law and Human Right No. 9/2011, a Notary has the authority to register fiduciary collateral deed electronically. The research used judicial normative method. The implementation of registering fiduciary collateral deed electronically has negative impact; the number of fiduciary deeds increases significantly, surpassing the natural limit, so that the deeds are most probably inauthentic. Therefore, supervision on a Notary should be more intensive, electronic fiduciary registration should be on line so that its authenticity can be kept safely and double fiduciary can be forestalled